2005
DOI: 10.1242/jeb.01730
|View full text |Cite
|
Sign up to set email alerts
|

Organic osmolytes as compatible, metabolic and counteracting cytoprotectants in high osmolarity and other stresses

Abstract: SUMMARY Organic osmolytes are small solutes used by cells of numerous water-stressed organisms and tissues to maintain cell volume. Similar compounds are accumulated by some organisms in anhydrobiotic, thermal and possibly pressure stresses. These solutes are amino acids and derivatives,polyols and sugars, methylamines, methylsulfonium compounds and urea. Except for urea, they are often called `compatible solutes', a term indicating lack of perturbing effects on cellular macromolecules and imply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
1,320
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,575 publications
(1,369 citation statements)
references
References 68 publications
35
1,320
0
14
Order By: Relevance
“…11 hydrostatic pressures 6,22 . In humans, osmolytes are of particular importance in the renal medulla 22 in which osmolarity may exceed osmolarity of plasma four times.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…11 hydrostatic pressures 6,22 . In humans, osmolytes are of particular importance in the renal medulla 22 in which osmolarity may exceed osmolarity of plasma four times.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…It has been found that osmolytes such as TMAO can enhance protein folding, ligand binding and can counteract perturbations caused by urea or inorganic ions [22][23][24] . Therefore, it is possible that TMAO affects the structure of receptors and peptide hormones such as Ang II, and may be not only a marker of increased cardiovascular risk, but also a mediator in etiology of cardiovascular diseases.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The functions of osmolytes like glycerol have long been assumed to include balancing high environmental osmolarity and stabilizing protein structure as a chemical chaperone (53,121). Glycerol synthesis is essential for long-term growth and reproduction of C. elegans on agar plates containing elevated NaCl (61).…”
Section: Extracellular Signaling Controls Organic Osmolytes and Osmosmentioning
confidence: 99%
“…Glycine betaine (GBT), trimethylamine N-oxide (TMAO) and choline are nitrogen-containing osmolytes (N-osmolytes) that are widely used by organisms in the marine environment to maintain favourable osmotic tension and positive turgor [1,2]. However, other roles for N-osmolytes are beginning to be elucidated.…”
Section: Introductionmentioning
confidence: 99%